The Effect of Combination of Increased Physical Activity and Verbal Communication on Life Satisfaction and Happiness of Couples - Shahmoradi, Zahra; Zargham Hajebi, Majid; Aghayousefi, Alireza (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This study aimed to determine the effect of combination of increased physical activity and verbal communication on life satisfaction and happiness of couples.Materials and Methods: The research method was quasi-experimental with pre-test and post-test followed up. The statistical population consisted of couples referring to counseling centers and psychological services under the supervision of well-being and the organization of the Psychological System of Qom in 2019, which numbered 558 couples. The sample required by convenience sampling from counseling centers and psychological services of Qom city was 60 couples who in the process of the study eventually reached 48 couples in 3 groups (15 couples in the intervention group increased physical activity with verbal communication, 16 couples in the intervention group of increased physical activity without verbal communication and 17 couples in the intervention group with no increased physical activity) were selected. For data collection, life satisfaction questionnaire (Deiner et al., 1985) and Oxford happiness questionnaire (Hill & Argyll 2002) were used. Interventions included increased physical activity based on Pour-Ranjbar and Nematollahzadeh Mahani protocol (2005), verbal communication based on sessions of verbal communication training program (Miller et al. 2004) and intervention of the researcher's proposed combined program. In this study, the data were analyzed by repeated measures analysis of variance using SPSS software version 25.Findings: The findings showed that the combination of increased physical activity with verbal communication had a significant effect on "life satisfaction" and "happiness of couples" with effect size of 0.31. The results of Tukey's post hoc test showed that the main factor in increasing life satisfaction and happiness of couples is increased physical activity with verbal communication. Also, the effect of increased physical activity on life satisfaction and happiness of couples was 0.23 and the effect of verbal communication on increasing life satisfaction and happiness of couples was estimated as 0.15.Conclusion: According to the results of the study, it can be concluded that combination of all three interventions, especially increased physical activity along with verbal communication, are effective methods for increasing life satisfaction and happiness of couples, and these interventions can be used as a combined intervention.